2010
DOI: 10.1186/1471-2377-10-34
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin is associated with mortality and outcome in patients with acute intracerebral hemorrhage

Abstract: BackgroundSpontaneous intracerebral hemorrhage (ICH) accounts for a high mortality and morbidity. Early prediction of outcome is crucial for optimized care and treatment decision. Copeptin, the C-terminal part of provasopressin, has emerged as a new prognostic marker in a variety of diseases, but its prognostic value in ICH is unknown.MethodsIn 40 consecutive patients who were admitted to the hospital within 72 hours after a spontaneous ICH, the plasma copeptin level was measured with a sandwich immunoassay up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 33 publications
4
46
0
1
Order By: Relevance
“…Although copeptin is not a specific marker, unlike other neuromarkers it directly bypasses the blood-brain barrier and is excreted into systemic circulation and thus it reflects the intracerebral condition better (14). A significant correlation has been shown between copeptin levels and prognosis and the GCS at presentation, not only in patients presenting with ischemic stroke but also for acute intracerebral hemorrhages (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although copeptin is not a specific marker, unlike other neuromarkers it directly bypasses the blood-brain barrier and is excreted into systemic circulation and thus it reflects the intracerebral condition better (14). A significant correlation has been shown between copeptin levels and prognosis and the GCS at presentation, not only in patients presenting with ischemic stroke but also for acute intracerebral hemorrhages (15).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high levels of copeptin allowed prediction of 30-day mortality (AUC of 0.88) and poor functional outcome at 90 days (AUC of 0.68) [80]. In a larger study, it was shown that copeptin independently predicted 1-year mortality and poor outcome as well as early neurologic deterioration [81].…”
Section: Selection Of Blood Biomarkers In Ichmentioning
confidence: 99%
“…Serum copeptin levels may correlate with the volume of brain edema, but this has not been confirmed [113]. Levels are positively correlated with hematoma volume, death at 30 days following ICH, and poor functional outcome at 3 months as measured by the mRS and the Barthel Index [113]. Vasopressin inhibitors have been investigated as a potential therapeutic intervention [114].…”
Section: Othersmentioning
confidence: 97%